Bioinspired Cell-Derived Nanovesicles versus Exosomes as Drug Delivery Systems: a Cost-Effective Alternative. Issue 1 (December 2017) - Goh, Wei; Zou, Shui; Ong, Wei; Torta, Federico; Alexandra, Alvarez; Schiffelers, Raymond; Storm, Gert; Wang, Jiong-Wei; Czarny, Bertrand; Pastorin, Giorgia
Abstract Cell Derived Nanovesicles (CDNs) have been developed from the rapidly expanding field of exosomes, representing a class of bioinspired Drug Delivery Systems (DDS). However, translation to clinical applications is limited by the low yield and multi-step approach in isolating naturally secreted exosomes. Here, we show the first demonstration of a simple and rapid production method of CDNs using spin cupsvia a cell shearing approach, which offers clear advantages in terms of yield and cost-effectiveness over both traditional exosomes isolation, and also existing CDNs fabrication techniques. The CDNs obtained were of a higher protein yield and showed similarities in terms of physical characterization, protein and lipid analysis to both exosomes and CDNs previously reported in the literature. In addition, we investigated the mechanisms of cellular uptake of CDNsin vitro and their biodistribution in anin vivo mouse tumour model. Colocalization of the CDNs at the tumour site in a cancer mouse model was demonstrated, highlighting the potential for CDNs as anti-cancer strategy. Taken together, the results suggest that CDNs could provide a cost-effective alternative to exosomes as an ideal drug nanocarrier.